2016
DOI: 10.1016/j.jcyt.2016.03.085
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness of Cord Blood Banking in Saudi Arabia

Abstract: Background. In the last decade, cord blood (CB) has proven to be a valuable source of hematopoietic stem cells for transplantation to treat many hematological disorders. Since then, many CB banks have been established worldwide. Our aim was to estimate the level of public awareness of CB banking in Saudi Arabia. Study Design and Methods. A self-administered questionnaire of 22 multiple choices was conveniently distributed, consisting of demographics, awareness measure, attitude toward banking preference, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Pandey and colleagues concluded that expectant mothers in their survey had very limited knowledge and undue expectations from UCB banking and their antenatal care providers should inform them about the pros and cons of the same [ 12 ]. A most recent study from Saudi Arabia suggested that women received the majority of information on UCB banking through social media and only 10% was through their obstetricians [ 13 ]. In addition to this, certain obstetric conditions require delayed cord clamping which must be discussed with the expectant parents.…”
Section: Discussionmentioning
confidence: 99%
“…Pandey and colleagues concluded that expectant mothers in their survey had very limited knowledge and undue expectations from UCB banking and their antenatal care providers should inform them about the pros and cons of the same [ 12 ]. A most recent study from Saudi Arabia suggested that women received the majority of information on UCB banking through social media and only 10% was through their obstetricians [ 13 ]. In addition to this, certain obstetric conditions require delayed cord clamping which must be discussed with the expectant parents.…”
Section: Discussionmentioning
confidence: 99%